Normothermic machine preservation of the liver: state of the art - Ceresa, C; Nasralla, D; Jassem, W (Springer International Publishing, 2018)
Purpose of Review This review aims to introduce the concept of normothermic machine perfusion (NMP) and its role in liver transplantation. By discussing results from recent clinical studies and highlighting the potential opportunities provided by this technology, we aim to provide a greater insight into NMP and the role it can play to enhance liver transplantation. Recent Findings NMP has recently been shown to be both safe and feasible in liver transplantation and has also demonstrated its superiority to traditional cold storage in terms of early biochemical liver function. Through the ability to perform a viability assessment during preservation and extend preservation times, it is likely that an increase in organ utilisation will follow. NMP may facilitate the enhanced preservation with improved outcomes from donors after cardiac death and steatotic livers. Furthermore, it provides the exciting potential for liver-directed therapeutic interventions. Summary Evidence to date suggests that NMP facilitates the enhanced preservation of liver grafts with improved early post-transplant outcomes. The key role for this technology is to increase the number and quality of liver grafts available for transplantation and to reduce waiting list deaths.